The Effect of Smoking on Oxygen Saturation Level of Patients Covid-19 - Yusuf Dwiyanto; Muhammad Didin Wahyudin; Ria Mariatul Isnaani; Dedeh Ernawati; Doddy Firmansyah; Noviana Haryanti; Rita Erlina; Nuzula Firdaus; Ali Asman Harahap; Agus Purnama; Satriani H Gultom (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: The Novel Coronavirus (Covid-19) disease caused by SARS-COV2 was first discovered in Wuhan, China, December 2019. WHO has set Covid 19 to be a pandemic which has resulted in an increase in death rates worldwide. Covid-19 attacks the respiratory system which resembles pneumonia but has signs of a decrease in oxygen saturation. In Indonesia, many people, especially men, practice smoking, where smoking can cause respiratory system problems, but there is no sign of a decrease in oxygen saturation. Objectives: This study aims to determine the effect of smoking on oxygen saturation levels in Covid-19 patients. Methods: This type of research is an analytic study with a cross sectional design. Total population of 52 people, with inclusion and exclusion criteria. Results: This study shows that 21.2% of patients who smoke 6-12 cigarettes / day have oxygen saturation <75%, with the result p-value = 0.000, which means that there is an effect between smoking on decreasing oxygen saturation, with a 53-fold chance of covid patients. People who smoke can cause a decrease in oxygen saturation. Conclusion: Decrease in oxygen saturation in covid-19 patients, can be caused due to the toxicity of cigarettes smoked. In smokers who are confirmed Covid-19, there will be an worsening of oxygen supply in the blood, which is indicated by a decrease in oxygen saturation <75%.